COMMUNICATION STRATEGIES IN DIGITAL DA’WAH: A CASE STUDY OF JANNAH INSTITUTE’S ISLAMIC EDUCATION FOR WOMEN - Hero Gefthi Firnando; Firman Abisyiwih (QAULAN: Journal of Islamic Communication, 2025)
This study aims to analyze the role of digital da'wah in Islamic education and the character development of Muslim women, with a case study of Jannah Institute. The research employs a qualitative approach using non-participatory observation and content analysis of da'wah materials delivered through digital platforms. The findings reveal that Jannah Institute adopts an interactive communication strategy, utilizes multimedia-based learning, and emphasizes Islamic values in daily life. Digital-based education enables broader access for Muslim women to understand Islamic teachings, although challenges remain in maintaining personal interactions as in conventional learning. In conclusion, effective digital da'wah in Islamic education requires adaptive communication strategies, appropriate technology utilization, and approaches tailored to audience needs. This study provides insights for scholars and preachers to optimize digital da'wah as a sustainable Islamic learning medium.